KAJIAN GENDER TENTANG DUNIA PENDIDIKAN DI MEDIA SOSIAL: PENELITIAN BIBLIOMETRIK BERBASIS DATA SCOPUS - Bahtiar, Ahmad; Hudaa, Syihaabul (Jurnal Harkat : Media Komunikasi Gender, 2025)
Abstract. The rapid development of social media has influenced various aspects of life, including education and gender construction. These issues have become increasingly complex in line with the growing use of digital media, thus requiring comprehensive scientific mapping. This study aims to map research trends on the theme of gender–education–social media based on metadata from articles indexed in the Scopus database during the period 1995–2023. The novelty of this research lies in its bibliometric approach to analyzing the evolution of keywords, author collaboration, and publication trends both thematically and spatially over a long time span. The data were analyzed using biblioshiny based on RStudio, following these steps: (1) searching for articles using specific keywords, (2) collecting metadata in Excel format, (3) processing the data through biblioshiny, and (4) conducting a descriptive bibliometric analysis. The scope of analysis includes the number of publications, author productivity, international collaboration networks, as well as thematic mapping and keyword evolution. This study is limited to metadata analysis without full-text content review and focuses only on articles available in the Scopus database. The results indicate that female authors dominate publications related to gender issues in Scopus. The most frequent collaborations occurred between authors from the USA–UK, USA–New Zealand, and USA–Canada. This mapping identifies emerging, stagnant, and potentially expandable themes. The study contributes to identifying research gaps and may serve as a foundation for further studies that explore the intersection of gender, education, and social media in more contextual and interdisciplinary ways. Abstrak. Perkembangan pesat media sosial telah memengaruhi berbagai aspek kehidupan, termasuk dunia pendidikan dan konstruksi gender. Isu-isu ini semakin kompleks seiring meningkatnya penggunaan media digital, sehingga memerlukan pemetaan ilmiah yang komprehensif. Penelitian ini bertujuan untuk memetakan tren riset bertema gender–pendidikan–media sosial berdasarkan metadata artikel yang terindeks dalam database Scopus selama periode 1995–2023. Kebaruan (novelty) dari riset ini terletak pada pendekatan bibliometrik dalam menganalisis evolusi kata kunci, kolaborasi penulis, dan tren publikasi secara tematik dan spasial dalam rentang waktu panjang. Data dianalisis menggunakan biblioshiny berbasis RStudio, dengan tahap: (1) pencarian artikel sesuai kata kunci, (2) pengumpulan metadata dalam format Excel, (3) pemrosesan data melalui biblioshiny, dan (4) analisis deskriptif bibliometrik. Ruang lingkup analisis mencakup jumlah publikasi, produktivitas penulis, jaringan kolaborasi antarnegara, serta peta tematik dan evolusi kata kunci. Batasan penelitian ini adalah tidak dilakukannya telaah isi penuh artikel serta keterbatasan pada artikel yang tersedia di database Scopus. Hasil menunjukkan bahwa penulis perempuan mendominasi publikasi terkait isu gender di Scopus. Kolaborasi paling sering terjadi antara penulis dari USA–UK, USA–New Zealand, dan USA–Canada. Pemetaan ini mengidentifikasi tema-tema yang berkembang, stagnan, dan potensial untuk digali lebih lanjut. Penelitian ini memberikan kontribusi dalam mengidentifikasi celah riset (research gap) serta dapat menjadi dasar untuk pengembangan studi lanjut yang mengkaji hubungan antara gender, pendidikan, dan media sosial secara lebih kontekstual dan lintas disiplin.